The bobsled push start: Influence on race outcome and push athlete talent identification and monitoring - Harrison, A. (2017)
Bobsled is an Olympic sport that has progressed from rudimentary in the 1800`s to highly technological replete with biomechanical analyses and investment in engineering from the world`s top engineers. Little to no investigation has been carried out on all the tracks and the interrelationship between various measures of starts and sled-travel down-track. Further, little quality research has been produced in the athletic characteristics required for high-level competition in bobsled.